The Influence of High Performance Work Systems (HPWS) On Innovative Work Behaviour Through Work Engagement - Husin, Noor Hassanah; Mansor, Nur Naha Abu; Kelana, Beni Widarman Yus (The journal of contemporary issues in business and government, 2021)
High performance work systems (HPWS) has dominated human resource management research on the importance of this bundle of HR practices to organizations. To date, research in this area has focused greatly on the organizational performance and innovation. However, mainstream HPWS research has paid little attention to employees‟ innovative work behaviour, or to the relationship between HPWS and work engagement. . Therefore the purpose of this study to investigate the relationship between HPWS and innovative work behaviour. This study also aims to examine the mediating role of work engagement between HPWS and innovative work behaviour. In this article, theory of job-demand resource used to describe the influence of HPWS as organizational resources on innovative work behaviour through work engagement. . The outcome of this study generates relevant information for organizations in recognizing the HPWS practices as well as enabling the organizations to highlight the most practical and significant HPWS implementation